2018
DOI: 10.1016/j.ijheatmasstransfer.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A pseudopotential multiphase lattice Boltzmann model based on high-order difference

Abstract: The hyperbolic tangent function is usually used as a reliable approximation of the equilibrium density distributions of a system with phase transitions. However, analyzing the accuracies of the numerical derivatives, we find that its numerical derivatives computed by central difference method (CDM) may deviate significantly from its analytical solutions, while those computed by high-order difference method (HDM) can agree very well. Therefore, we introduce HDM to evaluate the interparticle interactions instead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Eventually, the sheet breaks up and form secondary droplets. These observations are consistent to the previous reports [30,33]. The researchers also found that the spread radius r obeys the power law…”
Section: Droplet Splashing and Dynamic Galilean Invariancesupporting
confidence: 93%
See 1 more Smart Citation
“…Eventually, the sheet breaks up and form secondary droplets. These observations are consistent to the previous reports [30,33]. The researchers also found that the spread radius r obeys the power law…”
Section: Droplet Splashing and Dynamic Galilean Invariancesupporting
confidence: 93%
“…This results in a rather steep phase interface, which is similar to a hyperbolic tangent function. In these regions, CDM causes some considerable errors, and even makes mathematically equivalent formulas behave like different algorithms [30]. Therefore, it is necessary to introduce more accurate method to compute derivative and gradient in multiphase simulations, especially in the transition region.…”
Section: Derivative Computation By High-order Difference Methodsmentioning
confidence: 99%
“…Therefore, the boundary conditions, which must reflect the nonideal effect of the wetting boundary in multiphase simulations, should involve the consideration of the nonideal force; otherwise, the calculating errors are intolerable. Furthermore, in single-component two-phase systems, for example water and vapor, the liquid-gas density ratio can reach around 100 ∼ 1000 times, and the density profile across the phase transition region is nonlinear and approximate to a hyperbolic tangent curve [46], so the interpolation-based boundary conditions produce large calculating errors at three-phase contact regions. Even at the liquid-solid and gas-solid interfaces, the wetting boundaries would remarkably change the adjacent fluid density and lead to sizable interpolating errors.…”
Section: Curved Boundary Condition For Multiphase Flowmentioning
confidence: 99%
“…10 Although the angle deviation of the force can be reduced by high-order isotropic schemes and the spurious currents are reduced to a minimum level, it introduces more neighbor points, which makes the boundary realization more complicated and incurs additional computational costs [16,24]. Moreover, the accuracy of the discrete gradient mainly determines the errors in the numerical calculation of multiphase flow simulations, and the large numerical errors may make the simulation results inaccurate [70]. For example, it can be clearly seen from Fig.…”
Section: Nonideal Force Deviation and Spurious Currentsmentioning
confidence: 99%